Engineering Students' Reference of Low Enthalpy Geothermal Potential in Parangtritis. (March 2019) - Husna Rekinagara, Istifari; Mahfudz Prasetyo, Rizqi; Dwinagara, Barlian; Kunta Biddinika, Muhammad; Aziz, Muhammad; Takahashi, Fumitake
Abstract: Parangtritis is one of the seashore areas in Indonesia which has a low enthalpy geothermal potential. The possible utilizations suitable to this area is direct use, such as salt production, fish drying, saltwater desalination, and aquaculture. However, the utilization of this energy source is still not optimum yet. Considering the understanding on the technology as a key factor of renewable energy implementation, this paper examines how the geothermal potential and its utilization are understood by university students of Faculty of Mineral and Technology – one of main disciplines in geothermal field – in the Universitas Pembangunan Nasional "Veteran" Yogyakarta. In total, 100 respondents filled in the questionnaire. This study suggested the importance of understanding geothermal potential by Faculty of Mineral and Technology students in order to successfully utilize low enthalpy geothermal potential in Parangtritis and generally in Indonesia.